A novel approach to assess diet diversity: a development of the Nutritional Functional Diversity indicator - Di Maso, Matteo; Bravi, Francesca; Polesel, Jerry; Dal Maso, Luigino; Patel, Linia; La Vecchia, Carlo; Ferraroni, Monica (Frontiers in Nutrition, 2023)
Background and aims Diversity is a key element of diet quality. The Food Variety Score (FVS) is used to assess diversity, especially in low- and middle-income countries. It sums up the number of foods consumed ignoring their nutrient content. A more suitable index should combine the number of foods consumed and their nutritional composition. We adapted the Nutritional Functional Diversity indicator (NFD), proposed by ecologists, to measure diversity in the human diet. We compared NFD and FVS evaluating subjects’ distributions across quartiles of the two diversity indices. To evaluate which one reflected a higher diet quality, we estimated associations between these two diversity indices and diet quality measures, i.e., the Mediterranean Diet Score (MDS) and the Healthy Eating Index-2015 (HEI-2015). Associations were expressed by odds ratios (OR) and corresponding 95% confidence intervals (CI). Materials and methods We used the data of controls only derived from an integrated series of hospital-based case-control cancer studies conducted in different Italian areas. The NFD identifies groups of foods based on a set of nutrients according to a cluster analysis. Some steps are required: creating a food-nutrient matrix; clustering of the Euclidean food-food distance matrix to identify groups of foods with nutritional (dis)similarities; and calculating the NFD as the ratio between the sum of branch lengths of the dendrogram belonging to the number of foods consumed by individuals (i.e., subject-specific diversity) and the sum of all branch lengths of the dendrogram (i.e., maximal diversity). Results More than one quarter of individuals (28.4%) were differently classified within quartiles of the two diversity indices. For both indices, increasing the diversity level increased the risk for adhering to MDS (OR for NFD = 11.26; 95% CI: 7.88–16.09, and OR for FVS = 6.80; 95% CI: 4.84–9.54) and to HEI-2015 (OR for NDF = 2.86; 95% CI: 2.39–3.42, and OR for FVS = 2.72; 95% CI: 2.27–3.26). Associations were stronger for NFD. Conclusion Our findings showed a greater ability of NFD to assess diet quality quantifying the degree of diversity.